Transformational Leadership to Enhance Innovative Work Behavior through Organizational Learning Readiness and Knowledge Sharing Behavior as Mediating Variables among Employees of Brighton Real Estate Spazio Surabaya - Andi Ernanti Wahyuni Oktaviana; Amiartuti Kusmaningtyas; Siti Mujanah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to examine the role of transformational leadership in enhancing innovative work behavior through organizational learning readiness and knowledge sharing behavior as mediating variables among employees of Brighton Real Estate Spazio Surabaya. Employing a quantitative explanatory research design, data were collected through questionnaires distributed to 98 employees of Brighton Real Estate Spazio Surabaya. Data were analyzed using the Smart-PLS 3.2 software for hypothesis testing. The findings indicate that transformational leadership has a positive and significant effect (β = 0.311) on organizational learning readiness, and a positive and significant effect (β = 0.333) on knowledge sharing behavior. Organizational learning readiness also positively and significantly affects knowledge sharing behavior (β = 0.359). However, transformational leadership shows a negative and insignificant effect (β = −0.033) on innovative work behavior, while organizational learning readiness exhibits a positive but insignificant effect (β = 0.167) on innovative work behavior. Interestingly, knowledge sharing behavior demonstrates a negative and significant effect (β = −0.514) on innovative work behavior.